2017
DOI: 10.1111/anu.12561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplemental taurine on juvenile channel catfish Ictalurus punctatus growth performance

Abstract: Juvenile channel catfish (5.6 g/fish) were fed a basal diet that contained major protein (soybean meal, cottonseed meal) and energy (ground corn grain, wheat middlings) ingredients that were derived from plant sources. The basal diet was supplemented with three levels of crystalline taurine to provide 1, 2 and 5 g/kg taurine. In addition, a fifth diet that contained 80 g/kg menhaden fishmeal formulated with the same plant‐source ingredients was included as the positive control diet. Fish were fed the five diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…In most of the published studies, the positive effects of dietary taurine supplementation on the growth and feed utilization of fish were found, especially for the fish fed with plant protein-based diets. These fish species include white seabream (Diplodus sargus) (Magalhães et al 2019), turbot (Liu et al 2018;Sampath et al 2020;Wei et al 2018;Zhang et al 2019), rock bream (Oplegnathus fasciatus) (Ferreira et al 2014), common carp (Cyprinus carpio) (Abdel-Tawwab and Monier 2017), snapper (Lutjanus colorado) (Hernandez et al 2018), black carp (Mylopharyngodon piceus) (Zhang et al 2018) and channel catfish (Peterson and Li 2018). Furthermore, it was found that dietary methionine supplementation was inefficient in the plant-based diets to overcome the taurine deficiency for the growth performance of meagre (Argyrosomus regius).…”
Section: Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In most of the published studies, the positive effects of dietary taurine supplementation on the growth and feed utilization of fish were found, especially for the fish fed with plant protein-based diets. These fish species include white seabream (Diplodus sargus) (Magalhães et al 2019), turbot (Liu et al 2018;Sampath et al 2020;Wei et al 2018;Zhang et al 2019), rock bream (Oplegnathus fasciatus) (Ferreira et al 2014), common carp (Cyprinus carpio) (Abdel-Tawwab and Monier 2017), snapper (Lutjanus colorado) (Hernandez et al 2018), black carp (Mylopharyngodon piceus) (Zhang et al 2018) and channel catfish (Peterson and Li 2018). Furthermore, it was found that dietary methionine supplementation was inefficient in the plant-based diets to overcome the taurine deficiency for the growth performance of meagre (Argyrosomus regius).…”
Section: Growth Performancementioning
confidence: 99%
“…Taurine deficiency may lead to poor growth performance, green liver syndrome and psychological abnormalities of fish fed with fish meal-free diets (Takagi et al 2008). Moreover, there are many primary responses of fish that have been identified involving dietary taurine supplementation and include survival rate (Rotman et al 2017), growth performance (Poppi et al 2018;Zhang et al 2018), feed utilization (Al-Feky et al 2016b;Ferreira et al 2014;Peterson and Li 2018;Salze et al 2018b;Satriyo et al 2017), body composition (Hernandez et al 2018;Hoseini et al 2017), whole body taurine (Hoseini et al 2018;Salze et al 2018a;Stuart et al 2018), anti-oxidative capacity (Abdel-Tawwab and Monier 2018;Zhang et al 2018), immune response (Khaoian et al 2014;Kim et al 2017;Koven et al 2016;López et al 2015;Nguyen et al 2015;Richard et al 2017;Zhang et al 2019), cellular and metabolic responses (Feidantsis et al 2014), hyperplasia muscle growth (Sampath et al 2020), egg fertilization (Sarih et al 2019) and reproductive performance (Al-Feky et al 2016a;Guimaraes et al 2018). Taurine is a vital ingredient in fish nutrition, especially when feeding with plant protein-based diets.…”
Section: Introductionmentioning
confidence: 99%
“…This need for supplementation varies with species, fish developmental stage and diet composition (e.g. Gaylord et al 2006;Kim et al 2008;Lim et al 2013;Peterson and Li 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The dough was pelleted with help of hand pelletizer of 1 mm pellet size and stored in −20 C until use. The range of taurine in diet for pangasius was selected on the basis of taurine requirement in other freshwater fishes such as yellow catfish, channel catfish, African catfish, common carp, and rainbow trout which ranges between 2 and 20 g/kg diet (Abdel-Tawwab & Monier, 2018;Adeshina & Abdel-Tawwab, 2020;Gaylord et al, 2006;Li et al, 2016;Peterson & Li, 2018).…”
Section: Experimental Dietsmentioning
confidence: 99%
“…However, the absence of taurine in plant ingredients necessitates supplementation of taurine in aquafeeds to maintain production characteristics in terms of growth and feed efficiency (Salze & Davis, 2015). It is also reported that several freshwater fish species such as common carp, Cyprinus carpio, yellow catfish, Pelteobagrus fulvidraco, African catfish, Clarias garipenus, and channel catfish, Ictalurus punctatus, require exogenous taurine for optimum growth performance, feed consumption, digestion, assimilation, immunity, and other physiological functions (Abdel-Tawwab & Monier, 2018;Adeshina & Abdel-Tawwab, 2020;Li, Lai, Li, Gong, & Wang, 2016;Peterson & Li, 2018).…”
Section: Introductionmentioning
confidence: 99%